Intimate partner violence against women among contraceptive users at a primary health care setting in Southern Ethiopia: a facility-based cross-sectional study - Biniam Petros; Agumasie Semahegn; Simon Birhanu; Abdulmalik Abdela Bushura; Merhawi Gebremedhin (BMC, 2024)
Abstract Background One in three women experienced intimate partner violence (IPV) worldwide which has remained major public health challenge. Women's reproductive health service utilization has been seriously impacted by IPV. There is a paucity of evidence on the magnitude of IPV among contraceptive users in southern Ethiopia. Hence, the main aim of this study was to determine the level of IPV and its associated factors among married women who were contraceptive users in primary health care settings in Adilo Zuria district in southern Ethiopia. Methods A facility-based cross-sectional study was conducted among systematically recruited 405 married women who were contraceptive users in a primary health care setting in Adilo Zuria district in southern Ethiopia. Data were collected through face-to-face interviews using an adapted tool from existing literature including the World Health Organization IPV survey. Collected data were entered into EpiData 4.6 and exported to SPSS version 26 for cleaning and analysis. Descriptive and logistic regression analyses were performed to determine the level of IPV and identify factors associated with IPV. An adjusted odds ratio (AOR) from multiple logistic regression at a 95% confidence interval (CI) was used to declare a significant association. Results The prevalence of current IPV among contraceptive users was 72.6% (95% CI; 68.1-76.8%). Current psychological, physical, and sexual violence were 39.3%, 38.5%, and 31.9%, respectively. In multivariable analysis, women's being rural resident (AOR: 3.19, 95%CI: 1.69-6.02), women's formal education (AOR: 0.37, 95%CI: 0.19-0.70), partners alcohol consumption (AOR: 3.32, 95%CI: 1.89-5.84), partners Khat chewing (AOR: 7.22, 95%CI: 4.12-12.65) and poor social support (AOR: 2.47, 95%CI: 1.43-4.27) were significantly associated with current IPV against women. Conclusions Women's experience of IPV on contraceptive users was found to be unacceptably high in the study area. Women's being rural residents, having poor social support and partners who drank alcohol and Khat chewing were predictors of women's experience of IPV. Thus, interventions in improving women's educational status, strengthen the social support systems, and the behavior of partners who use stimulant substances are highly relevant to tackle IPV among contraceptive users in the primary healthcare setting.